Monte Carlo and Quasi-Monte Carlo Methods 2004
DOI: 10.1007/3-540-31186-6_19
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Quasi-Monte Carlo Simulation of Markov Chains with an Ordered State Space

Abstract: Summary. We study a randomized quasi-Monte Carlo method for estimating the state distribution at each step of a Markov chain with totally ordered (discrete or continuous) state space. The number of steps in the chain can be random and unbounded. The method can be used in particular to get a low-variance unbiased estimator of the expected total cost up to some random stopping time, when statedependent costs are paid at each step. We provide numerical illustrations where the variance reduction with respect to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…It is shown that uniformization, combined with a QMC method, 19 can be efficiently applied to the simulation of biochemical reaction networks when the aim is to compute transient solutions of the PDF. Two numerical examples have been considered, and the QMC method yields superior results.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is shown that uniformization, combined with a QMC method, 19 can be efficiently applied to the simulation of biochemical reaction networks when the aim is to compute transient solutions of the PDF. Two numerical examples have been considered, and the QMC method yields superior results.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…19 that the method yields unbiased estimators of averages and empirical variances. 19 that the method yields unbiased estimators of averages and empirical variances.…”
Section: Quasi-monte Carlo Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…and adding it to all the points of the sequence (modulo 1) [42] (see, also [43,44]). The integral is thus approximated via…”
Section: Complexity Of the Integration Problem For Korobov-like Spacesmentioning
confidence: 99%